Christian Theological Engagement with Islam: A Survey of Recent Publications. Issue 5 (3rd January 2022) - Marshall, David
Abstract: This article surveys the wide range of approaches to Christian theological engagement with Islam reflected in around 20 recent publications, focusing largely on monographs published from 2016 on. The works are discussed in the following categories: approaches to Islam in general; the Qur'an; Muhammad; Christology and soteriology; law, politics, and public life; and Orthodox approaches. As well as the ecclesial diversity of the authors – Roman Catholic, Orthodox, Protestant, evangelical – the survey covers varied theological approaches on a spectrum from "maximalist" to "minimalist" assessments of the extent of common ground between Christianity and Islam. The conclusion reflects on the Western provenance of the great majority of the studies surveyed and calls for more joined‐up thinking by Christian scholars working in this field.